Perceived Employability and Task Performance: Examining the Impact of Occupational Self Efficacy and Turnover Intention - Khalid, Dr. Komal (The journal of contemporary issues in business and government, 2021)
The aim of the study was to uncover the impact of occupational self-efficacy and employee’s turnover intention on perceived employability and task performance relationship. A sample of 80 project managers, 130 team leaders and 190 software developers working in the information technology sector were selected from Islamabad, Rawalpindi, Lahore and Karachi. The data collection was conducted through self- administered questionnaires and online survey. The results show that occupational self- efficacy has a positive influence on perceived employability and task performance relationship. It also reveals that occupational self-efficacy has a strong influence on perceived employability and turnover intention and turnover intention to task performance relationships. This research also indicates a stronger direct influence of occupational self- efficacy on perceived employability and task performance relationship as compared to the indirect influence of occupational self-efficacy on perceived employability to task performance via turnover intention relationship. The study suggests the importance of employee’s perceived employability to emphasize their intention to stay with the organization but it is often based on the perceive career guarantees from the organizations instead of their affection with the organization.